The Effect of Thermal Procedure on Skin Affected by Cellulite - Vasilevskaja, Simona; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
The external appearance, especially that of women, is very important and cellulite is an aesthetically unacceptable cosmetic defect (S. A. Abosabaa, 2020). Genetics, lifestyle, gender determines development of cellulite (N. Sadick, 2018).The aim. To evaluate the effect of thermal procedures on skin affected by cellulite.Methods. The analysis of 2010–2022 scientific literature in Journal of Cosmetic and Laser Therapy, Clinical, Cosmetic and Investigational Dermatology, Archives of Dermatological Research, PubMed electronic database was performed. The keywords helped to achieve the goal: cellulite, thermal procedures, cosmetic products. Ten scientific sources containing keywords were examined. A non-standardized interview method was used to examine eating habits, medications used, age, effectiveness of cosmetic products and a standardized customer card.Results. Thermal procedures decreased the volume of the abdomen by 11 cm, that of the buttocks and thighs affected by cellulite by 9 cm.Conclusions. 1. Cellulite mainly affected the skin of buttocks, thighs, and abdominal areas, the damage was influenced by the age, hormonal imbalance, diet, and a lack of physical activity. 2. The effectiveness of a thermal effect was observed after five procedures. After coordinating procedures with participants, changing eating habits and passive physical activity to active, cellulite stages decreased from stage III to stage II. 3. After ten thermal procedures, the participant reduced areas of the body affected by cellulite, restored the moisture level and firmness of the skin, however, cellulite did not disappear completely.
Keywords: cellulite; thermal procedures; cosmetic products; diet; physical activity